Factors that influence public awareness towards Takafulink Wanita Plan offered by MAA Takaful Berhad, Seremban branch / Noor Fariza Edora Zainudin - Zainudin, Noor Fariza Edora (Faculty of Business and Management, 2011)
This study is designed to investigate the public’s awareness towards Takafulink Wanita Plan offered by MAA Takaful Berhad Seremban Branch. Level of income, educational level and sales promotion are the independent variables. The dependent variable is public awareness towards Takafulink Wanita Plan. The objective of the study is to investigate the level of public awareness towards Takafulink Wanita Plan, secondly to determine whether there is correlation between independent variables and dependent variable and thirdly to determine the rank that influence public awareness towards Takafulink Wanita Plan. The data set in this study are collected among female employees that work nearby around 1kilometre from MAA Takaful Berhad, Seremban Branch through questionnaires. 100 respondents in that area had become the sample in this study by answering the questionnaires that randomly distributed. The findings indicate there is low level of public’s awareness towards Takafulink Wanita Plan offered by MAA Takaful Berhad. Besides, all the independent variables have correlation with the public’s awareness and educational level is the first rank that influence the public’s awareness towards Takafulink Wanita Plan. There are also several recommendations that researcher suggest based on the findings.